2013
DOI: 10.1002/mabi.201200482
|View full text |Cite
|
Sign up to set email alerts
|

BSAand Fibrinogen Adsorption on Chitosan/κ‐Carrageenan Polyelectrolyte Complexes

Abstract: PECs of chitosan/κ-carrageenan are prepared in three different volumetric rations. The complex formation is characterized in order to evaluate the blending formation. Blood compatibility is evaluated by protein adsorption (BSA and fibrinogen) and PEC toxicities are determined with fibroblast cell viability and proliferation. The swelling degree of PECs decreases when the amount of chitosan increases. Due to the linked film formation, PECs decrease BSA adsorption and increase fibrinogen adsorption when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…In this study, fetal bovine serum (FBS) containing more than 10,000 proteins (mainly albumin and immunoglobulin) was used to assess the protein adsorption capacity of our prepared scaffolds. As shown in Figure B, the CCG scaffolds absorbed more proteins than that of the CG scaffolds, which is due to the larger surface area of CCG scaffolds caused by the smaller pore size . In addition, ι‐CA is negatively charged under the physiological pH condition, creating an electrochemical environment favorable for the absorption of immunoglobulin (IgG) with the pI ranging from 7.4 to 8.6 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, fetal bovine serum (FBS) containing more than 10,000 proteins (mainly albumin and immunoglobulin) was used to assess the protein adsorption capacity of our prepared scaffolds. As shown in Figure B, the CCG scaffolds absorbed more proteins than that of the CG scaffolds, which is due to the larger surface area of CCG scaffolds caused by the smaller pore size . In addition, ι‐CA is negatively charged under the physiological pH condition, creating an electrochemical environment favorable for the absorption of immunoglobulin (IgG) with the pI ranging from 7.4 to 8.6 .…”
Section: Resultsmentioning
confidence: 99%
“…Carneiro et al [12] showed that increasing the amount of chitosan in the composition leads to a higher interaction of chitosan (attractive effect) than for carrageenan (repulsive effect) with plasma proteins. Xa.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The carrageenan solution was prepared by dissolving of 2 g of polymer in 100 mL of 0.5M KCl solution, according to the methodology proposed by Carneiro et al [12]. The PEC formation is considerably influenced by the interaction between the polyelectrolyte and metal ions.…”
Section: Preparation Of Pec Filmsmentioning
confidence: 99%
See 2 more Smart Citations